Assistance for 3R (Reduce, Reuse, Recycle) based waste management in Desa Wisata Selasari - Fransdito Ali Ilyas; Adil Ridlo Fadillah; Tedi Rustendi; Abdul Azis Ramadhan; Hadiyan Prayoga (Universitas Pendidikan Indonesia, 2025)
Selasari Village, as a leading tourist destination, faces crucial challenges, including a surge in seasonal waste volume that is not optimally managed due to limited infrastructure and limited public understanding of the 3R principles: Reduce, Reuse, and Recycle. This community service program aims to enhance community capacity, initiate source separation practices, and develop Standard Operating Procedures (SOP) adaptable to fluctuations in visitor numbers. Using a participatory approach that includes socialization, training in appropriate technologies such as composting and ecobricks, and intensive mentoring, this program actively engages tourism managers and local communities. The intervention results demonstrate a significant increase in partner awareness and participation, evidenced by the implementation of waste sorting, the revitalization of the